PENERAPAN BAHAN AJAR BERBASIS KETERAMPILAN BERPIKIR KRITIS - Hendra Nelva Saputra; Salim Salim (Nurul Jadid University, 2020)
This research aims to determine the application of teaching materials based on the skills of critical thinking in the Learning class XI SMA Negeri 1 Pasarwajo. This type of research is research quasi-experiment with design pretest-posttest group design. The treatment class consists of two classes, which are experimental classes taught with critical thinking skill-based teaching and control class taught with the teaching materials used by learners. The Data is analyzed by using the gain score normalized and continued with the Independent sample T-test at a level of significance of 5%. The results of this study showed a graph of increased experimental class critical thinking skills taught using critical thinking skill-based teaching materials are always higher than the control class taught with the teaching materials commonly used by learners in schools. Different test results (t-test) average Gain normalized critical thinking skills learn to demonstrate a significant difference between learning after receiving learning by using the teaching materials based on critical thinking skills compared to using teaching materials commonly used learners in schools with tvalue = 6, 322 is greater than this ttable = 1.671 at a = 0.05.